Nanofiltration membrane, preparation method thereof and filtering device

By using different oil phase monomers for interfacial polymerization during the preparation of nanofiltration membrane, the charge density, pore size and separation layer thickness of the membrane are coordinated to regulate the problem of difficulty in balancing the index of nanofiltration membrane in the prior art, efficient removal of mineral ions and organic pollutants, and improving the cleaning resistance and service life of the membrane.

CN119793223AActive Publication Date: 2025-04-11TSINGHUA UNIVERSITY +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510118959.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-11
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to achieve balance in the three important indicators of nanofiltration membrane pore size, membrane surface charge density and separation layer thickness, resulting in poor results in drinking water depth treatment and terminal drinking water treatment.

Method used

By using two oil phase monomers with different physical and chemical properties during the preparation of the nanofiltration membrane, the first oil phase monomer and the second oil phase monomer, the amidation reaction and graft reaction are carried out in the early and later stages of the interface polymerization reaction, and the interface polymerization reaction time is extended to more than 30 seconds to coordinate the negative charge density, pore size and separation layer thickness of the nanofiltration membrane.

Benefits of technology

The nanofiltration membrane is achieved with high retention selectivity and chemical cleaning resistance, improving the removal efficiency of mineral ions and organic pollutants, and extending the service life of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793223A_ABST
    Figure CN119793223A_ABST
Patent Text Reader

Abstract

The invention provides a nanofiltration membrane, a preparation method thereof and a filtering device, and the preparation method of the nanofiltration membrane comprises the following steps: infiltrating a polymer-based membrane in a water-phase solution containing a water-phase monomer so as to infiltrate the water-phase monomer on the surface of the polymer-based membrane; applying an oil-phase solution containing a first oil-phase monomer and a second oil-phase monomer to the surface of the polymer-based membrane infiltrated with the water-phase monomer so as to generate an interfacial polymerization reaction, and forming a separation layer on the surface of the polymer-based membrane; carrying out post-treatment on the separation layer to prepare the nanofiltration membrane; wherein the time of the interfacial polymerization reaction is longer than 30s; the first oil-phase monomer and the second oil-phase monomer can be respectively subjected to amidation reaction with the water-phase monomer; the molecular weight of the second oil-phase monomer is smaller than that of the first oil-phase monomer, the binding capacity of the second oil-phase monomer and the water-phase monomer is larger than that of the first oil-phase monomer and the water-phase monomer, and the reaction capacity of the second oil-phase monomer and the water-phase monomer is not smaller than that of the first oil-phase monomer and the water-phase monomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of nanofiltration membrane preparation, and in particular to a nanofiltration membrane and a preparation method and a filtration device thereof. Background Art

[0002] Nanofiltration is a pressure-driven membrane separation technology between ultrafiltration and reverse osmosis. Nanofiltration has been widely used in the fields of deep drinking water treatment and terminal drinking water treatment, and has broad application prospects. The ideal nanofiltration membrane for drinking water treatment should have a moderate molecular weight cutoff and as high a negative charge density on the membrane surface as possible. Nanofiltration membranes that meet this feature have high "mineral ion / organic pollutant" retention selectivity, that is, they can efficiently remove natural organic matter and organic micropollutants in water, while retaining mineral ions such as calcium, magnesium, and bicarbonate in water that are beneficial to pipeline distribution, drinking water taste, and human health.

[0003] In addition, nanofiltration membranes are fouled during their use. Membrane fouling refers to the phenomenon and process in which the separation or water flow performance of the membrane is reduced due to the deposition of particulate or dissolved substances in the water on the membrane surface and inside the membrane material, or the growth of microorganisms on the membrane surface. Chemical cleaning is the main means of removing membrane fouling. Generally speaking, the thicker the separation layer of the membrane, the more conducive it is to withstand the negative impact of membrane cleaning on the membrane material, that is, the longer the service life of the membrane.

[0004] When using the traditional interfacial polymerization reaction method to prepare nanofiltration membranes, it is difficult to achieve a balance in the three important indicators of membrane pore size, membrane surface charge density and separation layer thickness to make it suitable for deep drinking water treatment and terminal drinking water treatment.

[0005] Therefore, a method for preparing a nanofiltration membrane that can take into account the membrane pore size, the negative charge density on the membrane surface, and the thickness of the separation layer is provided. Summary of the invention

[0006] Based on this, the present application provides a nanofiltration membrane and a preparation method and a filtration device thereof that can take into account good membrane pore size, membrane surface negative charge density and separation layer thickness.

[0007] The first aspect of the present application provides a method for preparing a nanofiltration membrane, comprising the following steps:

[0008] Immersing the polymer base film in an aqueous solution containing an aqueous monomer to wet the surface of the polymer base film with the aqueous monomer;

[0009] Applying an oil phase solution containing a first oil phase monomer and a second oil phase monomer on the surface of the polymer base film soaked with the water phase monomer to cause an interfacial polymerization reaction to form a separation layer on the surface of the polymer base film; the interfacial polymerization reaction time is greater than 30 seconds;

[0010] Post-treating the separation layer to prepare the nanofiltration membrane;

[0011] Among them, the first oil phase monomer and the second oil phase monomer can respectively undergo amidation reaction with the water phase monomer; the molecular weight of the second oil phase monomer is smaller than the molecular weight of the first oil phase monomer, the binding ability of the second oil phase monomer with the water phase monomer is greater than the binding ability of the first oil phase monomer with the water phase monomer, and the reaction ability of the second oil phase monomer with the water phase monomer is not less than the reaction ability of the first oil phase monomer with the water phase monomer.

[0012] In some embodiments, the second oil phase monomer comprises an aliphatic acyl halide containing two acyl halide functional groups;

[0013] Optionally, the second oil phase monomers include one or more carbonyl halides;

[0014] Further optionally, the second oil phase monomer includes one or more of oxalyl chloride, malonyl chloride, succinyl chloride, and adipoyl chloride.

[0015] In some embodiments, the first oil phase monomer comprises an aromatic acyl halide containing multiple acyl halide functional groups;

[0016] Optionally, the first oil phase monomer includes one or more of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride and phthaloyl chloride.

[0017] In some embodiments, the weight ratio of the first oil phase monomer to the second oil phase monomer is (0.01-0.2):(0.01-0.2); and / or

[0018] The mass proportion of the first oil phase monomer in the oil phase solution is 0.01wt%-0.2wt%; and / or

[0019] The mass proportion of the second oil phase monomer in the oil phase solution is 0.01wt%-0.2wt%; and / or

[0020] The organic solvent contained in the oil phase solution includes one or more of n-hexane, cyclohexane, n-heptane, petroleum ether and isoparaffin.

[0021] In some embodiments, the weight percentage of the aqueous phase monomer in the aqueous phase solution is 0.05 wt % to 5 wt %; and / or

[0022] The aqueous phase monomers include polyamines;

[0023] Optionally, the aqueous phase monomer includes one or more of aliphatic polyamines and aromatic polyamines;

[0024] Further optionally, the aliphatic polyamine includes one or more of piperazine, methylpiperazine, ethylpiperazine, methyl piperazinecarboxylate, ethyl piperazinecarboxylate, ethylenediamine, propylenediamine, butylenediamine and pentanediamine;

[0025] Further optionally, the aromatic polyamine includes one or more of m-phenylenediamine, p-phenylenediamine, mesitylenetriamine, diaminobenzoic acid and diaminobenzenesulfonic acid.

[0026] In some embodiments, the material of the polymer-based membrane includes one or more of polysulfone, polyethersulfone, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyethylene, polypropylene and ceramic materials; and / or

[0027] The polymer-based film also contains a nonwoven fabric support layer.

[0028] In some embodiments, the post-treatment includes a thermal curing treatment;

[0029] Optionally, before the step of heat curing treatment, the method further includes: performing solvent activation treatment on the separation layer.

[0030] The second aspect of the present application provides a nanofiltration membrane, which is prepared using the nanofiltration membrane preparation method of the first aspect of the present application.

[0031] In some embodiments, the nanofiltration membrane comprises a polymer-based membrane and a separation layer located on the surface of the polymer-based membrane, and the thickness of the separation layer is ≥100 nm, and can be 100 nm-200 nm;

[0032] Optionally, the nanofiltration membrane has at least one of the following features (1)-(3):

[0033] (1) The surface of the nanofiltration membrane has a negative charge;

[0034] (2) The surface of the nanofiltration membrane has a negative charge, and the absolute value of the Zeta potential of the surface of the nanofiltration membrane is ≥40 mV under the condition of a pH value of 6.5-7.5;

[0035] (3) The cut-off molecular weight of the nanofiltration membrane is 200Da-300Da.

[0036] The third aspect of the present application provides a filtration device, comprising the nanofiltration membrane of the second aspect of the present application.

[0037] The above-mentioned method for preparing the nanofiltration membrane comprises a first oil phase monomer and a second oil phase monomer having different physical and chemical properties in the oil phase solution, so that in the initial stage of the interfacial polymerization reaction, the first oil phase monomer mainly participates in the amidation reaction and the cross-linking reaction is mainly performed, and in the later stage of the interfacial polymerization reaction, the second oil phase monomer mainly participates in the amidation reaction and the grafting reaction is mainly performed, and at the same time, the interfacial polymerization reaction time is extended to more than 30 seconds, thereby simultaneously increasing the negative charge density on the surface of the nanofiltration membrane, reducing the pore size of the nanofiltration membrane, and increasing the thickness of the separation layer. The prepared nanofiltration membrane has the advantages of high retention selectivity and resistance to chemical cleaning. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0039] Figure 1 The water permeability coefficients of Comparative Example 1, Example 1, Example 2, Example 3 and Example 4, as well as xylose, MgCl 2 , NaCl retention rate;

[0040] Figure 2 The water permeability coefficients of Comparative Example 1, Example 5, Example 6, Example 7 and Example 8 and the xylose, MgCl 2 , NaCl retention rate;

[0041] Figure 3 is the cut-off molecular weight of Comparative Example 1, Example 1, Example 5, Example 6, Example 7 and Example 8;

[0042] Figure 4 is the thickness of the separation layer in the nanofiltration membranes of Comparative Example 1, Example 1, Example 5, Example 6, Example 7 and Example 8;

[0043] Figure 5 The water permeability coefficients of Comparative Examples 1, 2, 3, 4 and 5 and the xylose, MgCl 2 , NaCl retention rate;

[0044] Figure 6 The water permeability coefficients of Examples 1, 9, 10, 11 and 12 and the xylose, MgCl 2 , NaCl retention rate;

[0045] Figure 7The water permeability coefficients of Comparative Examples 6, 7, 8, 9 and 10 and the xylose, MgCl 2 , NaCl retention rate;

[0046] Figure 8 The water permeability coefficients of Comparative Examples 11, 12, 13, 14 and 15 and the xylose, MgCl 2 、Na 2S O 4 The interception rate;

[0047] Fig. 9 This is a comparison diagram of zeta potentials measured under neutral pH conditions (pH=7) for Comparative Example 2, Comparative Example 5, Comparative Example 11, Comparative Example 14, Example 9, and Example 12;

[0048] Fig.10 It is a comparison chart of nitrogen and oxygen content on the active layer surface of Comparative Example 2, Comparative Example 1, Example 9 and Example 1 measured by XPS;

[0049] Fig.11 is the thickness of the separation layer in the nanofiltration membranes of Comparative Example 2, Comparative Example 5, Comparative Example 6, Comparative Example 9, Example 9, Example 10, Example 12 and Example 1;

[0050] Fig.12 The water permeability coefficients of Comparative Example 1, Example 1 and Comparative Example 16 and xylose, MgCl 2 , NaCl retention rate;

[0051] Fig.13 is the thickness of the separation layer in the nanofiltration membranes of Comparative Example 1, Example 1 and Comparative Example 16. DETAILED DESCRIPTION

[0052] For ease of understanding of the present invention, the application will be described more fully below with reference to relevant embodiments. The following provides preferred embodiments of the application. However, the application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.

[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0054] The terms "and / or", "or / and", and "and / or" used herein include any one of two or more related listed items, and also include any and all combinations of the related listed items, wherein the any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that in the present application, the technical solution undoubtedly includes technical solutions connected by "logical and", and also undoubtedly includes technical solutions connected by "logical or".

[0055] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0056] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0057] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0058] The temperature parameters in this application, unless otherwise specified, allow both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0059] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the ability to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.

[0060] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0061] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0062] In the description of the application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0063] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0064] If there is no special explanation, all the steps of the present application can be performed sequentially or randomly, preferably sequentially.

[0065] The interfacial polymerization method is currently the "gold standard" for the preparation of nanofiltration membranes. The most commonly used aqueous monomer is piperazine (PIP), and the most commonly used oil-phase monomer is trimesoyl chloride (TMC). When using the traditional interfacial polymerization method to prepare nanofiltration membranes, it is difficult to achieve a balance in the three important indicators of membrane pore size, membrane surface charge density, and separation layer thickness to make it suitable for deep treatment of drinking water and terminal drinking water treatment. For example, by adjusting the conditions of the interfacial polymerization reaction, the pore size of the membrane can be reduced and the thickness of the separation layer can be increased, but at the same time, the negative charge density on the membrane surface will be reduced. The negative charge density on the surface of the nanofiltration membrane can be increased by adopting the "secondary reaction method", but the thickness of the separation layer will be significantly reduced, and sometimes the pore size of the membrane will be increased. In addition, the secondary reaction method will also increase the membrane preparation process and significantly increase the cost of membrane preparation.

[0066] Therefore, a method for preparing a nanofiltration membrane that can take into account the membrane pore size, membrane surface charge density, and separation layer thickness is provided.

[0067] Based on the above problems, the present application adopts two oil phase monomers with different physical and chemical properties in the process of preparing nanofiltration membranes, so that differentiated oil phase monomer competitive reactions can be achieved during the interfacial polymerization reaction, thereby achieving coordinated regulation of the negative charge density on the surface of the nanofiltration membrane, the membrane pore size and the thickness of the separation layer, which is beneficial to improving the "mineral ion / organic pollutant" retention selectivity of the nanofiltration membrane and at the same time enhancing the chemical cleaning resistance of the nanofiltration membrane.

[0068] One or more embodiments of the present application provide a method for preparing a nanofiltration membrane, comprising the following steps:

[0069] The polymer base membrane is immersed in an aqueous phase solution containing an aqueous phase monomer to impregnate the surface of the polymer base membrane with the aqueous phase monomer; an oil phase solution containing a first oil phase monomer and a second oil phase monomer is applied to the surface of the polymer base membrane impregnated with the aqueous phase monomer to cause an interfacial polymerization reaction to form a separation layer on the surface of the polymer base membrane; and the separation layer is post-treated to prepare a nanofiltration membrane;

[0070] Among them, the time of interfacial polymerization reaction is greater than 30s; the first oil phase monomer and the second oil phase monomer can respectively undergo amidation reaction with the water phase monomer; the molecular weight of the second oil phase monomer is smaller than the molecular weight of the first oil phase monomer, the binding ability of the second oil phase monomer with the water phase monomer is greater than the binding ability of the first oil phase monomer with the water phase monomer, and the reaction ability of the second oil phase monomer with the water phase monomer is not less than the reaction ability of the first oil phase monomer with the water phase monomer.

[0071] It should be noted that the molecular weight of the second oil phase monomer is smaller than that of the first oil phase monomer, that is, the molecular weight of the second oil phase monomer is smaller, which is beneficial to the mass transfer of the second oil phase monomer in the reaction zone.

[0072] The binding capacity of the second oil phase monomers with the water phase monomers is greater than that of the first oil phase monomers with the water phase monomers, that is, the second oil phase monomers with the water phase monomers have sufficient non-chemical reaction binding capacity, which is manifested in that the non-chemical reaction binding enthalpy change between the second oil phase monomers and the water phase monomers is lower than the non-chemical reaction binding enthalpy change between the first oil phase monomers and the water phase monomers, so that the water phase monomers can diffuse farther, which is beneficial to increase the thickness of the reaction zone and ultimately increase the thickness of the membrane separation layer.

[0073] The amidation reaction ability of the second oil phase monomer with the water phase monomer is not less than that of the first oil phase monomer with the water phase monomer, which is manifested in that the amidation reaction energy barrier between the second oil phase monomer and the water phase monomer is not higher than the amidation reaction energy barrier between the first oil phase monomer and the water phase monomer, which is conducive to the second oil phase monomer being able to undergo a grafting reaction with the water phase monomer or residual amino groups on the primary separation layer in the later stage of the interfacial polymerization reaction. Among them, the primary separation layer is mainly formed after the first oil phase monomer reacts with the water phase monomer.

[0074] The interfacial polymerization reaction time mentioned above refers to the time after the oil phase solution is applied to the surface of the polymer base film and before the post-treatment. The extended interfacial polymerization reaction time is conducive to the second oil phase monomer being able to fully undergo a grafting reaction with the water phase monomer or the residual amino group on the primary separation layer in the later stage of the reaction, thereby facilitating an increase in the thickness of the separation layer.

[0075] It can be understood that in the preparation method of the nanofiltration membrane provided by the present application, the oil phase solution includes a first oil phase monomer and a second oil phase monomer with different physical and chemical properties, so that in the initial stage of the interfacial polymerization reaction, the first oil phase monomer mainly participates in the amidation reaction and the cross-linking reaction is mainly, and in the later stage of the interfacial polymerization reaction, the second oil phase monomer mainly participates in the amidation reaction and the grafting reaction is mainly, and at the same time, the interfacial polymerization reaction time is extended to more than 30s, thereby simultaneously increasing the negative charge density on the surface of the nanofiltration membrane, reducing the pore size of the nanofiltration membrane, and increasing the thickness of the separation layer. The prepared nanofiltration membrane has the advantages of high retention selectivity and cleaning resistance.

[0076] In this application, "first oil phase monomer", "second oil phase monomer", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0077] In some embodiments, the second oil phase monomer includes an aliphatic acyl halide containing multiple acyl halide functional groups. Optionally, the number of acyl halide functional groups contained in the aliphatic acyl halide is 2.

[0078] As a possible implementation, the second oil phase monomer includes one or more carbonyl halides. It should be noted that carbonyl halides refer to compounds containing carbonyl groups (C=O) and halogen atoms, and the carbon atom in the carbonyl group is connected to the halogen atom.

[0079] In some exemplary embodiments, the second oil phase monomer includes one or more of oxalyl chloride, malonyl chloride, succinyl chloride, and adipoyl chloride.

[0080] As a possible embodiment, the mass ratio of the first oil phase monomer to the second oil phase monomer is (0.01-0.2):(0.01-0.2); for example, it can be but not limited to 0.01:0.2, 0.02:0.2, 0.04:0.2, 0.06:0.2, 0.08:0.2, 0.1:0.2, 0.12:0.2, 0.14:0.2, 0.16:0.2, 0.18:0.2, 0.2:0.2, 0.2:0.18, 0.2:0.16, 0.2:0.14, 0.2:0.12, 0.2:0.1, 0.2:0.08, 0.2:0.06, 0.2:0.04, 0.2:0.02, 0.2:0.01 or the range between any two of the above ratios. When the mass ratio of the first oil phase monomer to the second oil phase monomer is within the above range, the formation of the primary separation layer in the initial stage of the interfacial polymerization reaction will not be affected, and the cut-off molecular weight of the primary separation layer is moderate.

[0081] In some optional embodiments, the mass proportion of the first oil phase monomer in the oil phase solution is 0.01wt%-0.2wt%; for example, it can be but not limited to 0.01wt%, 0.02wt%, 0.05wt%, 0.1wt%, 0.15wt%, 0.17wt%, 0.2wt% or a range between any two of the above mass proportions, etc. When the mass proportion of the first oil phase monomer in the oil phase solution is within the above range, it will not affect the formation of the primary separation layer in the initial stage of the interfacial polymerization reaction, and the cut-off molecular weight of the formed primary separation layer is moderate.

[0082] In some embodiments, the first oil phase monomer includes an aromatic acyl halide containing multiple acyl halide functional groups. The number of acyl halide functional groups contained in the aromatic acyl halide is 2 or more, which is conducive to making the formed separation layer polymer a network cross-linked structure.

[0083] In some optional embodiments, the first oil phase monomer includes one or more of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride and phthaloyl chloride.

[0084] As a possible implementation, the mass proportion of the second oil phase monomer in the oil phase solution is 0.01wt%-0.2wt%; for example, it can be but not limited to 0.01wt%, 0.02wt%, 0.05wt%, 0.1wt%, 0.15wt%, 0.17wt%, 0.2wt% or a range between any two of the above mass proportions, etc. When the mass proportion of the second oil phase monomer in the oil phase solution is within the above range, it is beneficial for the second oil phase monomer to fully exert its corresponding role in the initial and later stages of the interfacial polymerization reaction.

[0085] In some embodiments, the mass percentage of the aqueous phase monomer in the aqueous phase solution is 0.05wt%-5wt%; for example, it can be but not limited to 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt% or a range between any two of the above mass percentages, etc. When the mass percentage of the aqueous phase monomer in the aqueous phase solution is within the above range, it will not affect the formation of the primary separation layer in the initial stage of the interfacial polymerization reaction, and the cut-off molecular weight of the formed primary separation layer is moderate.

[0086] As a possible implementation, the water phase monomer includes polyamine.

[0087] In some alternative embodiments, the water phase monomer includes one or more of an aliphatic polyamine and an aromatic polyamine.

[0088] In some optional embodiments, the aliphatic polyamine includes one or more of piperazine, methylpiperazine, ethylpiperazine, methyl piperazinecarboxylate, ethyl piperazinecarboxylate, ethylenediamine, propylenediamine, butylenediamine, and pentylenediamine.

[0089] In some exemplary embodiments, the aromatic polyamine includes one or more of m-phenylenediamine, p-phenylenediamine, mesitylenetriamine, diaminobenzoic acid, and diaminobenzenesulfonic acid.

[0090] In some embodiments, the material of the polymer-based membrane includes one or more of polysulfone, polyethersulfone, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyethylene, polypropylene, and ceramic materials.

[0091] In some exemplary embodiments, the polymer-based film further comprises a nonwoven support layer.

[0092] As a possible implementation manner, the organic solvent contained in the oil phase solution includes one or more of n-hexane, cyclohexane, n-heptane, petroleum ether and isoparaffin.

[0093] In some embodiments, the post-treatment includes a heat curing treatment to further promote the interfacial polymerization reaction of the remaining mixed acyl halide monomers and the residual amino groups. As a non-limiting example, the temperature of the heat curing treatment is 40°C-80°C and the time is 1 min-10 min.

[0094] In some optional embodiments, before the step of heat curing treatment, the method further includes: performing a solvent activation treatment on the separation layer.

[0095] As a non-limiting example, the separation layer is subjected to solvent activation treatment by applying an organic solvent such as normal alkane, cycloalkane, isoalkane, petroleum ether or alcohol on the formed separation layer.

[0096] One or more embodiments of the present application provide a nanofiltration membrane, which is prepared by the above-mentioned method for preparing a nanofiltration membrane. The nanofiltration membrane has the characteristics of high retention selectivity and resistance to cleaning.

[0097] In some embodiments, the nanofiltration membrane includes a polymer base membrane and a separation layer located on the surface of the polymer base membrane, and the thickness of the separation layer is ≥100 nm, thereby helping to improve the chemical cleaning resistance of the nanofiltration membrane.

[0098] In some optional embodiments, the thickness of the separation layer is 100nm-200nm; for example, it can be but not limited to 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 150nm, 170nm, 180nm, 190nm, 200nm or a range between any two of the above thicknesses, etc.

[0099] In some embodiments, the surface of the nanofiltration membrane carries a negative charge; thus, it is helpful to improve the "mineral ion / organic pollutant" retention selectivity of the nanofiltration membrane.

[0100] As a possible implementation, the surface of the nanofiltration membrane carries a negative charge, and the absolute value of the Zeta potential of the nanofiltration membrane surface is ≥40mV under the condition of a pH value of 6.5-7.5; thereby, it is helpful to further improve the "mineral ion / organic pollutant" retention selectivity of the nanofiltration membrane.

[0101] In some optional embodiments, the cut-off molecular weight of the nanofiltration membrane is 200Da-300Da, for example, but not limited to 200Da, 210Da, 220Da, 230Da, 240Da, 250Da, 260Da, 270Da, 280Da, 290Da, 300Da or a range between any two of the above cut-off molecular weights, etc. This is conducive to further improving the "mineral ion / organic pollutant" retention selectivity of the nanofiltration membrane.

[0102] One or more embodiments of the present application provide a filtration device, comprising the above-mentioned nanofiltration membrane.

[0103] The technical scheme of the present invention is described in detail below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for which specific conditions are not specified in the following embodiments are preferably referred to the guidance given in the present invention, and can also be carried out according to the experimental manual or conventional conditions in the art, or according to the conditions recommended by the manufacturer, or with reference to experimental methods known in the art.

[0104] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.

[0105] 1. Preparation of Nanofiltration Membrane

[0106] Example 1

[0107] The polysulfone-based membrane was immersed in a 0.6 wt% piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.02 wt% oxalyl chloride (second oil phase monomer) and 0.1 wt% trimesoyl chloride (first oil phase monomer) for 1 min; then, the membrane was taken out and thermally cured at 65°C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0108] Example 2

[0109] The polysulfone-based membrane was immersed in a 0.6 wt% piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.04 wt% oxalyl chloride (second oil phase monomer) and 0.1 wt% trimesoyl chloride (first oil phase monomer) for 1 min; then, the membrane was taken out and thermally cured at 65°C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0110] Example 3

[0111] The polysulfone-based membrane was immersed in a 0.6 wt% piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.05 wt% oxalyl chloride (second oil phase monomer) and 0.1 wt% trimesoyl chloride (first oil phase monomer) for 1 min; then, the membrane was taken out and thermally cured at 65°C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0112] Example 4

[0113] The polysulfone-based membrane was immersed in a 0.6 wt% piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.06 wt% oxalyl chloride (second oil phase monomer) and 0.1 wt% trimesoyl chloride (first oil phase monomer) for 1 min; then, the membrane was taken out and thermally cured at 65°C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0114] Example 5

[0115] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.04 wt % succinyl chloride (second oil phase monomer) and 0.1 wt % trimesoyl chloride (first oil phase monomer) for 1 min; then, the membrane was taken out and thermally cured at 65°C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0116] Example 6

[0117] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.05 wt % succinyl chloride (second oil phase monomer) and 0.1 wt % trimesoyl chloride (first oil phase monomer) for 1 min; then, the membrane was taken out and thermally cured at 65°C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0118] Example 7

[0119] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.04 wt % adipoyl chloride (second oil phase monomer) and 0.1 wt % trimesoyl chloride (first oil phase monomer) for 1 min; then, the membrane was taken out and thermally cured at 65°C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0120] Example 8

[0121] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.05 wt % adipoyl chloride (second oil phase monomer) and 0.1 wt % trimesoyl chloride (first oil phase monomer) for 1 min; then, the membrane was taken out and thermally cured at 65°C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0122] Example 9

[0123] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.02 wt % oxalyl chloride (second oil phase monomer) and 0.1 wt % trimesoyl chloride (first oil phase monomer) for 10 s; then, the membrane was taken out and thermally cured at 65 °C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0124] Example 10

[0125] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.02 wt % oxalyl chloride (second oil phase monomer) and 0.1 wt % trimesoyl chloride (first oil phase monomer) for 20 s; then, the membrane was taken out and thermally cured at 65 °C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0126] Embodiment 11

[0127] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.02 wt % oxalyl chloride (second oil phase monomer) and 0.1 wt % trimesoyl chloride (first oil phase monomer) for 30 s; then, the membrane was taken out and thermally cured at 65 °C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0128] Example 12

[0129] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.02 wt % oxalyl chloride (second oil phase monomer) and 0.1 wt % trimesoyl chloride (first oil phase monomer) for 45 s; then, the membrane was taken out and thermally cured at 65 °C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0130] Comparative Example 1

[0131] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a 0.1 wt % n-hexane solution of trimesoyl chloride (the first oil phase monomer) for 1 min; then, the membrane was taken out and thermally cured at 65 ° C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0132] Comparative Example 2

[0133] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a 0.1 wt % hexane solution of trimesoyl chloride (the first oil phase monomer) for 10 s; then, the membrane was taken out and thermally cured at 65 ° C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0134] Comparative Example 3

[0135] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a 0.1 wt % hexane solution of trimesoyl chloride (the first oil phase monomer) for 20 s; then, the membrane was taken out and thermally cured at 65 ° C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0136] Comparative Example 4

[0137] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a 0.1 wt % hexane solution of trimesoyl chloride (the first oil phase monomer) for 30 s; then, the membrane was taken out and thermally cured at 65 ° C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0138] Comparative Example 5

[0139] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a 0.1 wt % hexane solution of trimesoyl chloride (the first oil phase monomer) for 45 s; then, the membrane was taken out and thermally cured at 65 ° C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0140] Comparative Example 6

[0141] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.05 wt % isophthaloyl chloride (the first oil phase monomer) and 0.1 wt % trimesoyl chloride (the first oil phase monomer) for 10 s; then, the membrane was taken out and thermally cured at 65°C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0142] Comparative Example 7

[0143] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.05 wt % isophthaloyl chloride (the first oil phase monomer) and 0.1 wt % trimesoyl chloride (the first oil phase monomer) for 20 s; then, the membrane was taken out and thermally cured at 65 ° C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0144] Comparative Example 8

[0145] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.05 wt % isophthaloyl chloride (the first oil phase monomer) and 0.1 wt % trimesoyl chloride (the first oil phase monomer) for 30 s; then, the membrane was taken out and thermally cured at 65 °C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0146] Comparative Example 9

[0147] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.05 wt % isophthaloyl chloride (the first oil phase monomer) and 0.1 wt % trimesoyl chloride (the first oil phase monomer) for 45 s; then, the membrane was taken out and thermally cured at 65°C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0148] Comparative Example 10

[0149] The polysulfone-based membrane was immersed in a 0.6 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.05 wt % isophthaloyl chloride (the first oil phase monomer) and 0.1 wt % trimesoyl chloride (the first oil phase monomer) for 1 min; then, the membrane was taken out and thermally cured at 65°C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0150] Comparative Example 11

[0151] The polysulfone-based membrane was immersed in a 2.0 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.05 wt % sulfonyl chloride and 0.1 wt % trimesoyl chloride (first oil phase monomer) for 10 s; then, the membrane was taken out and thermally cured at 65 °C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0152] Comparative Example 12

[0153] The polysulfone-based membrane was immersed in a 2.0 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.05 wt % sulfonyl chloride and 0.1 wt % trimesoyl chloride (first oil phase monomer) for 20 s; then, the membrane was taken out and thermally cured at 65 °C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0154] Comparative Example 13

[0155] The polysulfone-based membrane was immersed in a 2.0 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.05 wt % sulfonyl chloride and 0.1 wt % trimesoyl chloride (first oil phase monomer) for 30 s; then, the membrane was taken out and thermally cured at 65 °C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0156] Comparative Example 14

[0157] The polysulfone-based membrane was immersed in a 2.0 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.05 wt % sulfonyl chloride and 0.1 wt % trimesoyl chloride (first oil phase monomer) for 45 s; then, the membrane was taken out and thermally cured at 65 °C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0158] Comparative Example 15

[0159] The polysulfone-based membrane was immersed in a 2.0 wt % piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.05 wt % sulfonyl chloride and 0.1 wt % trimesoyl chloride (first oil phase monomer) for 1 min; then, the membrane was taken out and thermally cured at 65°C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0160] Comparative Example 16

[0161] The polysulfone-based membrane was immersed in a 0.6 wt% piperazine aqueous solution (aqueous phase solution) for 2 min to remove excess aqueous solution on the surface; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.1 wt% trimesoyl chloride (the first oil phase monomer) for 1 min; then, the interfacial polymerization reaction was carried out in a n-hexane solution containing 0.02 wt% oxaloyl chloride (the second oil phase monomer) for 1 min; then, the membrane was taken out and thermally cured at 65°C for 4 min; finally, the prepared nanofiltration membrane was rinsed with deionized water and the filtration performance was tested.

[0162] The raw materials and preparation parameters of Examples 1-12 and Comparative Examples 1-16 are shown in Table 1.

[0163] Table 1

[0164]

[0165] 2. Performance Test

[0166] The nanofiltration membranes prepared in the above-mentioned embodiments and comparative examples were tested using a laboratory-scale cross-flow filtration system. The system had three parallel filtration units. The effective area of ​​each cell was 20.6 cm 2 . Three separate membrane pieces cut from the same membrane were used in parallel experiments. Before sampling, the membrane had to be pre-compressed at 8 bar for at least 30 min to ensure its stability. Subsequent tests were carried out under cross-flow conditions with an operating pressure of 0.5 MPa and a water temperature of 20℃-25℃. The ionic strength of the inorganic salt solutions used in the tests was 10 mmol / L, and the concentrations of the single solute solutions of glycerol, xylose, glucose, and sucrose were all 100 mg / L (their retention rates were used to calculate the cut-off molecular weight and pore size of the composite nanofiltration membrane). The xylose retention rate was determined by a TOC analyzer. The thickness of the separation layer in the selected nanofiltration membrane was measured by TEM (transmission electron microscopy). The element distribution on the surface of the selected nanofiltration membrane was measured by XPS (x-ray photoelectron spectroscopy).

[0167] Depend on Figure 1It can be seen that under the operating pressure of 0.5 MPa, the water permeability coefficient of Examples 1-4 is 3.0 L m -2 h -1 bar -1 Increased to 3.9 L m -2 h -1 bar -1 , 4.0 L m -2 h -1 bar -1 , 4.4 L m -2 h -1 bar -1 5.2L m -2 h -1 bar -1 , which indicates that as the concentration of oxalyl chloride increases, the separation layer of the nanofiltration membrane gradually becomes loose, and the corresponding xylose retention rate also decreases from 75% in Comparative Example 1 to 63%, 47%, 38%, and 32%, respectively. In addition, the salt retention rate of the nanofiltration membrane also decreased significantly, but it is worth noting that compared with the sodium chloride retention rate, which only decreased from 50.5% in Comparative Example 1 to 33.7% in Example 4, the magnesium chloride retention rate decreased more significantly, from 75.0% in Comparative Example 1 to 17.2% in Example 4, and the magnesium chloride retention rates in Examples 1-4 were all lower than the sodium chloride retention rate, which is an obvious feature of a strong negatively charged membrane.

[0168] Depend on Figure 2 It can be seen that, similarly, by adding succinyl chloride and adipoyl chloride to the traditional acyl chloride monomer, the prepared nanofiltration membrane has a similar retention performance to that of Examples 1-4, and all show a trend that the retention rate of magnesium chloride is less than the retention rate of sodium chloride, indicating that a series of small molecule organic diacyl chlorides can effectively improve the negative charge of the nanofiltration membrane surface within a certain concentration range. The reason for this is that: the small molecule organic diacyl chloride mainly undergoes an amidation grafting reaction in the later stage of the interfacial polymerization reaction, and the remaining acyl chloride groups undergo a hydrolysis reaction to generate carboxyl groups, thereby making the surface of the nanofiltration membrane negatively charged.

[0169] Depend on Figure 3 It can be seen that compared with the cut-off molecular weight of 200.3 Da in the comparative example, the cut-off molecular weights of Example 1, Example 5, Example 6, Example 7 and Example 8 dropped to 236.5 Da, 257.6 Da, 277.5 Da, 263.0 Da and 276.3 Da, respectively. However, the cut-off molecular weight is still less than 300 Da, and a relatively high retention level is still maintained for organic pollutants. It can be seen that the nanofiltration membrane prepared based on the blending of small molecule organic polyacyl halide monomers has a relatively high retention selectivity of "calcium and magnesium ions / organic pollutants".

[0170] At the same time, by Figure 4 It can be seen that compared with the thickness of 83.6 nm in the nanofiltration membrane of Comparative Example 1, the thickness of the separation layer in the nanofiltration membrane of Example 1, Example 5, Example 6, Example 7 and Example 8 increased to 138.0 nm, 127.2 nm, 119.3 nm, 121.3 and 117.4 nm, respectively, indicating that the blending of small molecule organic polyacyl halide monomers effectively increases the thickness of the separation layer in the nanofiltration membrane, which is beneficial to the stable operation of the nanofiltration membrane under long-term cleaning.

[0171] Depend on Figure 5 and Figure 6 It can be seen that as the reaction time increases, the water flux of comparative examples 1-5 decreases, and the corresponding xylose retention rate and salt retention rate increase slightly, but in general, it has little effect on the performance of traditional nanofiltration membranes prepared from only a single oil phase monomer. On the other hand, the nanofiltration membrane prepared by mixing small molecule organic diacyl chlorides has a significant impact on the reaction time: in a short time (10 s-30 s), small molecule organic diacyl chlorides cannot effectively increase the negative charge density on the membrane surface, and the magnesium chloride retention rates of Examples 9-10 are much greater than sodium chloride; further extending the reaction time, only when the reaction time is greater than 30 s, can small molecule organic diacyl chlorides increase the negative charge density on the membrane surface, and the magnesium chloride retention rates of Examples 1 and Examples 11-12 are all less than the sodium chloride retention rate.

[0172] Depend on Figure 7 and 8 It can be seen that when aromatic diacyl chloride (isophthaloyl chloride) and sulfonyl halide (sulfonyl chloride) are used as the second oil phase monomer and added to the oil phase solution of traditional acyl chloride monomer for interfacial polymerization reaction with different reaction times, the magnesium chloride retention rate of the prepared aromatic diacyl chloride blended membrane increases with the extension of reaction time, while the sulfonyl halide blended membrane always maintains a high retention rate for magnesium chloride. Obviously, the two blended membranes cannot reduce the retention rate for calcium and magnesium ions, and cannot meet the high selective separation performance of "calcium and magnesium ions / organic pollutants".

[0173] Depend on Fig. 9 It can be seen that extending the interfacial polymerization reaction time has little effect on the surface charge of the nanofiltration membrane in the comparative example, which all exhibits weak negative charge; however, the Zeta potential of the nanofiltration membrane prepared by mixing small molecule organic diacyl chlorides decreases from -32 mV at 10 s to -50 mV at 45 s under the condition of pH value of 6.5-7.5, indicating that the negative charge density on the surface of the nanofiltration membrane in Example 12 has been significantly enhanced.

[0174] Depend on Fig.10It can be seen that due to the interference of the small molecule organic diacyl chloride in a short time, more nitrogen elements diffused to the membrane surface, and as the interfacial polymerization reaction time increased, more small molecule organic diacyl chlorides tended to participate in the interfacial polymerization reaction mainly in the form of grafting, so the oxygen content on the surface of the nanofiltration membrane in Example 1 increased significantly. Fig.11 It can be seen that due to the mechanism of small molecule organic diacyl chloride interfering first and then reacting, a loose layer formed by grafting and cross-linking of small molecule organic diacyl chloride and residual piperazine will be formed on the surface of the relatively dense separation layer formed in a short time, which will significantly increase the thickness of the separation layer in the nanofiltration membrane. Fig.12 and 13 It can be seen that the performance of the nanofiltration membrane made by one-step blending of small molecule organic diacyl chlorides was compared with that of the nanofiltration membrane made by two-step grafting of oil phase monomers. Since the small molecule organic diacyl chlorides have a smaller molecular structure, they can easily enter the primary separation layer formed by interfacial polymerization of traditional aqueous phase monomers and oil phase monomers, and undergo amidation reaction with residual amino groups. Although the two-step grafting of oil phase monomers to prepare nanofiltration membranes can also increase the negative charge density on the membrane surface and reduce the cut-off molecular weight of the membrane, the thickness of the separation layer in the prepared nanofiltration membrane is relatively small, which is far from the thickness of the separation layer in the nanofiltration membrane made by one-step blending of small molecule organic diacyl chlorides.

[0175] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0176] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a nanofiltration membrane, characterized in that: The steps include: Immersing the polymer base film in an aqueous solution containing an aqueous monomer to wet the surface of the polymer base film with the aqueous monomer; Applying an oil phase solution containing a first oil phase monomer and a second oil phase monomer on the surface of the polymer base film soaked with the water phase monomer to cause an interfacial polymerization reaction to form a separation layer on the surface of the polymer base film; the interfacial polymerization reaction time is greater than 30 seconds; Post-treating the separation layer to prepare the nanofiltration membrane; Among them, the first oil phase monomer and the second oil phase monomer can respectively undergo amidation reaction with the water phase monomer; the molecular weight of the second oil phase monomer is smaller than the molecular weight of the first oil phase monomer, the binding ability of the second oil phase monomer with the water phase monomer is greater than the binding ability of the first oil phase monomer with the water phase monomer, and the reaction ability of the second oil phase monomer with the water phase monomer is not less than the reaction ability of the first oil phase monomer with the water phase monomer.

2. The preparation method according to claim 1, characterized in that The second oil phase monomer includes an aliphatic acyl halide containing two acyl halide functional groups; Optionally, the second oil phase monomers include one or more carbonyl halides; Further optionally, the second oil phase monomer includes one or more of oxalyl chloride, malonyl chloride, succinyl chloride, and adipoyl chloride.

3. The preparation method according to claim 1, characterized in that: The first oil phase monomer includes an aromatic acyl halide containing multiple acyl halide functional groups; Optionally, the first oil phase monomer includes one or more of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride and phthaloyl chloride.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the first oil phase monomer to the second oil phase monomer is (0.01-0.2):(0.01-0.2); and / or The mass proportion of the first oil phase monomer in the oil phase solution is 0.01wt%-0.2wt%; and / or The mass proportion of the second oil phase monomer in the oil phase solution is 0.01wt%-0.2wt%; and / or The organic solvent contained in the oil phase solution includes one or more of n-hexane, cyclohexane, n-heptane, petroleum ether and isoparaffin.

5. The preparation method according to claim 1, characterized in that: The mass proportion of the aqueous phase monomer in the aqueous phase solution is 0.05wt%-5wt%; and / or The aqueous phase monomers include polyamines; Optionally, the aqueous phase monomer includes one or more of aliphatic polyamines and aromatic polyamines; Further optionally, the aliphatic polyamine includes one or more of piperazine, methylpiperazine, ethylpiperazine, methyl piperazinecarboxylate, ethyl piperazinecarboxylate, ethylenediamine, propylenediamine, butylenediamine and pentanediamine; Further optionally, the aromatic polyamine includes one or more of m-phenylenediamine, p-phenylenediamine, mesitylenetriamine, diaminobenzoic acid and diaminobenzenesulfonic acid.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The material of the polymer-based membrane includes one or more of polysulfone, polyethersulfone, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyethylene, polypropylene and ceramic materials; and / or The polymer-based film also contains a nonwoven fabric support layer.

7. The preparation method according to any one of claims 1 to 5, characterized in that: The post-treatment includes a thermal curing treatment; Optionally, before the step of heat curing treatment, the method further includes: performing solvent activation treatment on the separation layer.

8. A nanofiltration membrane, characterized in that: The preparation method is described in any one of claims 1 to 8.

9. The nanofiltration membrane according to claim 8, characterized in that The nanofiltration membrane comprises a polymer base membrane and a separation layer located on the surface of the polymer base membrane, and the thickness of the separation layer is ≥100nm, and can be optionally 100nm-200nm; Optionally, the nanofiltration membrane has at least one of the following features (1)-(3): (1) The surface of the nanofiltration membrane has a negative charge; (2) The surface of the nanofiltration membrane has a negative charge, and the absolute value of the Zeta potential of the surface of the nanofiltration membrane is ≥40 mV under the condition of a pH value of 6.5-7.5; (3) The cut-off molecular weight of the nanofiltration membrane is 200Da-300Da.

10. A filtering device, characterized in that: The filtration device comprises the nanofiltration membrane according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Preparation process of nanofiltration composite membrane

    CN113368713A

  • Preparation method of multi-layer stepped polyamide composite separation membrane

    CN115569526A

  • High-selectivity nanofiltration composite membrane and preparation method thereof

    CN115888428A

  • Nanofiltration membrane as well as preparation method and application thereof

    CN117619175A